Metal composite bipolar plate and processing method and application thereof

By adopting a composite plate structure of titanium/titanium alloy and aluminum/aluminum alloy, the combination of bipolar plate runner structure and adjustment interface is improved, and the problem of bipolar plates prone to cracking or warping during stamping and forming is solved, and the production cost is reduced, and the performance and market competitiveness of bipolar plates are improved.

CN119742388AActive Publication Date: 2025-04-01TRIO METAL (GZ) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510241630.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-01
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

The existing PEM electrolytic cell bipolar plates are prone to fracture or warping at the corners of the runner during stamping and forming, and the material cost is high and the manufacturing cost is high, which affects the market competitiveness of the system.

Method used

Titanium/titanium alloy and aluminum/aluminum alloy are used to form composite plates. By improving the flow channel structure of the bipolar plate and adjusting the interface combination method of the composite laminate plate, the fracture or warping at the runner corners are avoided during the stamping process, and the performance of the bipolar plates is improved and the production cost is reduced through welding and annealing treatment.

Benefits of technology

It effectively avoids the fracture and warping problems at the corners of the runner, improves the performance and stability of the bipolar plate, and reduces production costs and improves the market competitiveness of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742388A_ABST
    Figure CN119742388A_ABST
Patent Text Reader

Abstract

The invention discloses a metal composite bipolar plate and a processing method and application thereof.The metal composite bipolar plate comprises a middle metal plate layer, bipolar plate structure layers are welded to the upper surface and the lower surface of the middle metal plate layer respectively, and the middle metal plate layer is fully wrapped in the bipolar plate structure layers; the middle metal plate layer and the bipolar plate structure layer are made of different metal materials; atomic diffusion layers exist on bonding interfaces between the upper surface and the lower surface of the middle metal plate layer and the bipolar plate structure layer; a plurality of flow channels are formed in the surface of the bipolar plate structure layer through stamping, and corners at the bottoms of the flow channels and corners at openings are all arranged to be of chamfer structures. Titanium / titanium alloy and aluminum / aluminum alloy are adopted to form composite plate combination, the runner of the bipolar plate is improved, and the interface combination mode of the composite laminate is adjusted, so that the corner of the runner is prevented from being cracked or warped in the stamping process, meanwhile, the performance of the bipolar plate is improved, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal composite materials and processing technology, and in particular to a metal composite bipolar plate and a processing method and application thereof. Background Art

[0002] In the proton exchange membrane (PEM) electrolyzer system, bipolar plates occupy a pivotal position. They are not only an indispensable conductive bridge between electrolysis units, but also responsible for guiding the flow of reactants, collecting generated gases, and providing the necessary structural stability. The design and material selection of bipolar plates for PEM electrolyzers are directly related to electrolysis efficiency, system durability, and overall economic feasibility, and are one of the key factors in promoting the development of the hydrogen energy economy. Therefore, the research and development of high-performance and cost-effective bipolar plate technology is of great significance to accelerating the commercialization of PEM electrolyzer technology.

[0003] Traditionally, PEM electrolyzer bipolar plates are made of corrosion-resistant and highly conductive metals or alloys, such as stainless steel, titanium or their alloys. These materials, with their excellent physical and chemical properties, can effectively cope with the harsh electrochemical environment and corrosive challenges during the electrolysis process. However, the high material costs and complex processing, especially in large-scale production, significantly increase the manufacturing cost of bipolar plates, which in turn affects the market competitiveness of PEM electrolyzer systems. The combination of material costs and precision manufacturing processes has become a major obstacle to the widespread application of PEM electrolyzer technology.

[0004] In recent years, with the continuous progress of materials science, especially the breakthrough development of composite materials technology, the design and material selection of bipolar plates for PEM electrolyzers are undergoing a profound change. This provides unprecedented opportunities to reduce system costs and improve electrolysis efficiency. As a potential bipolar plate material, metal-based composite materials combine the advantages of multiple metals or alloys, such as high strength, high conductivity and excellent corrosion resistance. While ensuring the efficient operation of PEM electrolyzers, they also meet multiple functional requirements such as gas separation, liquid management and structural support.

[0005] At present, commercial PEMFC bipolar plates on the market are mainly made of graphite, which has a high production cost, resulting in high cost and heavy weight of the bipolar plate stack. Metal bipolar plates have the advantages of light weight, small size and low manufacturing cost, and are the preferred material for hydrogen fuel cell bipolar plates. At present, the commonly used methods for bipolar plate forming include hydraulic forming, laser engraving and stamping. Among them, the stamping process has high production efficiency, low cost and is easy to achieve large-scale automated production. However, with the improvement of the requirements for bipolar plate forming, metal bipolar plates tend to be ultra-thin, flow channels are complicated and miniaturized, which makes it easy for metal bipolar plates to crack or warp when forming at the flow channel corners during the stamping process; therefore, micro-deformation processing and warping control during the stamping process are issues that need to be focused on. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the purpose of the present application is to provide a metal composite bipolar plate, which is formed by combining titanium / titanium alloy and aluminum / aluminum alloy to form a composite plate, and by improving the bipolar plate flow channel and adjusting the interface bonding method of the composite layer plate, it is possible to avoid cracking or warping at the flow channel corners during the stamping process, while improving the performance of the bipolar plate and reducing the production cost.

[0007] To solve the above problems, the technical solutions adopted in this application are as follows: An embodiment of the present application provides a metal composite bipolar plate, comprising an intermediate metal plate layer, wherein the upper surface and the lower surface of the intermediate metal plate layer are respectively welded with a bipolar plate structural layer, the intermediate metal plate layer is fully wrapped in the bipolar plate structural layer, the intermediate metal plate layer material is aluminum or an aluminum alloy, and the bipolar plate structural layer material is titanium or a titanium alloy; an atomic diffusion layer exists at the bonding interface between the upper surface and the lower surface of the intermediate metal plate layer and the bipolar plate structural layer; a plurality of flow channels are formed on the surface of the bipolar plate structural layer by stamping, and the corners at the bottom of the flow channel and the corners at the opening are both set as chamfered structures.

[0008] As a further preferred solution, the total thickness of the metal composite bipolar plate described in the embodiment of the present application is 2-12 mm, wherein the ratio of the thickness of the bipolar plate structure layer to the thickness of the intermediate metal plate layer is 1:(2-5).

[0009] As a further preferred solution, the average thickness of the atomic diffusion layer described in the embodiment of the present application is 5-20 μm.

[0010] As a further preferred solution, the width of the flow channel described in the embodiment of the present application is 1.2~2.0 mm, and the depth is 0.5~0.8 mm; the angle formed by the side of the flow channel and the bottom is 135°~175°.

[0011] As a further preferred scheme, the flow channel described in the embodiment of the present application is divided into a gas transition zone, a reaction zone and a drainage transition zone on the surface of the bipolar plate structure layer; wherein the gas transition zone adopts a multi-branch mesh flow field, the reaction zone adopts a wavy flow field, and the drainage transition zone adopts a point flow field structure.

[0012] As a further preferred scheme, the metal composite bipolar plate described in the embodiment of the present application is provided with a water inlet hole on one side and a water outlet hole on the other side, the water inlet hole and the water outlet hole are located at diagonal positions of the metal composite bipolar plate, and the flow channel connects the water inlet hole and the water outlet hole; the metal composite bipolar plate is also provided with air holes for gas to pass through.

[0013] The present application also provides a method for processing a metal composite bipolar plate, which solves the problem that the flow channel corners are prone to cracking or warping during the stamping process by improving the stamping method, and combines welding and annealing to improve the performance of the bipolar plate. The processing method includes the following steps: Pretreatment: Cut the intermediate metal sheet and bipolar plate sheet to the appropriate size, clean and ensure that the surface of the metal material is clean and pollution-free; Stamping: Stamp the bipolar plate sheet in steps to form a flow channel on its surface, so that the corners at the bottom of the flow channel and the intersections at the opening are chamfered to obtain a bipolar plate structure layer; Welding composite: fix the middle metal plate, place the bipolar plate structure layer plates on the upper and lower surfaces of the middle metal plate respectively, weld the bipolar plate structure layer plates and the middle metal plate together by welding, and wrap the middle metal plate inside the bipolar plate structure layer to obtain a composite metal plate with a bipolar plate structure; Annealing treatment: the composite metal plate is subjected to annealing treatment, and after cooling, a metal composite bipolar plate is obtained.

[0014] As a further preferred solution, in the pretreatment process of the processing method, ultrasonic cleaning is used to clean the intermediate metal plate and the bipolar plate, and the cleaning medium is analytical pure anhydrous ethanol.

[0015] As a further preferred scheme, the stamping forming process of the processing method adopts step-by-step stamping forming; in the first step of stamping, a first punch with a semicircular or arc-shaped end is used to stamp simultaneously on the upper and lower surfaces of the bipolar plate, and the clamping force is set to 300kN~350kN, and the stroke is 40~65SPM; in the second step of stamping, a second punch with a first arc chamfered end is used to stamp simultaneously on the upper and lower surfaces of the bipolar plate, and the clamping force is set to 320kN~360kN, and the stroke is 40~65SPM, and the radius r of the first arc chamfer and the width L of the second punch satisfy r1=1 / 4L2; in the third step of stamping, a third punch with a second arc chamfered end is used to stamp simultaneously on the upper and lower surfaces of the bipolar plate, and the radius r2 of the second arc chamfer and the width L3 of the third punch satisfy r2=1 / 9L3, the clamping force is set to 320kN~380kN, and the stroke is 40~65SPM.

[0016] As a further preferred scheme, the intermediate metal plate described in the processing method is an aluminum or aluminum alloy plate, and the bipolar plate structural layer plate is a titanium or titanium alloy plate; laser welding is adopted in the welding composite, and the welding conditions are: the laser power is 4~6kW, and the spot diameter is 0.18~0.25mm; before welding, the intermediate metal plate and the bipolar plate structural layer plate are preheated, and the preheating temperature is controlled between 350℃~450℃.

[0017] As a further preferred scheme, the intermediate metal plate described in the processing method is an aluminum or aluminum alloy plate, and the bipolar plate plate is a titanium or titanium alloy plate; when the welding composite is performed, diffusion welding is adopted, and the welding conditions are: the welding temperature is set to 540~560℃, the pressure is 5.5~7MPa, and the time is 60-90min.

[0018] As a further preferred solution, during the annealing treatment in the processing method, the temperature is set to 490° C. to 520° C. and the duration is 20 min to 30 min.

[0019] The embodiments of the present application also provide an application of a metal composite bipolar plate in manufacturing a PEM electrolyzer.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. In the metal composite bipolar plate described in the embodiment of the present application, the intermediate metal plate layer and the bipolar plate structural layer are made of different metal materials, which can fully utilize the advantages of their respective materials. The selection of the intermediate metal plate layer material can be adjusted according to the actual application scenario, and the bipolar plate structural layer can be made of corrosion-resistant and easy-to-process materials, which not only improves the overall performance of the bipolar plate, such as conductivity, corrosion resistance and mechanical strength; but also reduces the cost of the material.

[0021] 2. In the metal composite bipolar plate described in the embodiment of the present application, the intermediate metal plate layer and the bipolar plate structure layer are connected by welding, and an atomic diffusion layer exists at the bonding interface between the two, which helps to enhance the bonding strength between the two layers and prevent delamination or falling off due to stress concentration or environmental factors during use.

[0022] 3. In the metal composite bipolar plate described in the embodiment of the present application, the bottom corners and the corners at the opening of the bipolar plate structure layer are formed by stamping on the surface of the bipolar plate structure layer. This design helps to optimize the flow characteristics of the fluid, reduce the resistance and eddy current of the fluid in the flow channel, and improve the fluid transmission efficiency; it can also avoid problems such as cracking or warping at the flow channel corners during the flow channel stamping. At the same time, this chamfered structure can also reduce the scouring and corrosion of the bipolar plate surface by the fluid, and extend the service life of the bipolar plate.

[0023] 4. In the processing method of the metal composite bipolar plate described in the embodiment of the present application, a flow channel is formed on the surface of the bipolar plate by step-by-step stamping, and the corners at the bottom of the flow channel and the corners at the opening are chamfered, which not only optimizes the flow characteristics of the fluid and reduces the fluid resistance, but also solves the problem of easy cracking and warping at the flow channel corners during the stamping process.

[0024] 5. In the processing method of the metal composite bipolar plate described in the embodiment of the present application, the bipolar plate structure layer plate and the intermediate metal plate are firmly welded together by welding, so that the intermediate metal plate is fully wrapped inside the bipolar plate structure layer, thereby enhancing the overall strength and stability of the bipolar plate and ensuring its reliability in the application environment.

[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 This is a schematic diagram of the structure of the metal composite bipolar plate described in an embodiment of the present application.

[0028] Figure 2 This is a cross-sectional view in the thickness direction of the metal composite bipolar plate described in an embodiment of the present application.

[0029] Figure 3 This is a SEM image of the cross-section of the metal composite bipolar plate described in Example 1 of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] The term "comprising" and other equivalent descriptions involved in the specification and claims of this application are intended to cover non-exclusive inclusions, including both the contents clearly described in the specification and claims, and the steps or units that are not described in the specification and claims but are inherent in the product, method or structure.

[0032] The embodiment of the present application provides a metal composite bipolar plate, including an intermediate metal plate layer, wherein the upper and lower surfaces of the intermediate metal plate layer are respectively welded with bipolar plate structural layers, wherein the intermediate metal plate layer material is aluminum or aluminum alloy, and the bipolar plate structural layer material is titanium or titanium alloy; titanium or titanium alloy is selected as the material of the bipolar plate structure, which has the characteristics of excellent corrosion resistance, high strength and low density, etc. In the application of proton exchange membrane (PEM) electrolyzer, the corrosion resistance of titanium is better than that of stainless steel and aluminum alloy, which helps to extend the service life of the bipolar plate and reduce the maintenance cost of the battery system; using aluminum or aluminum alloy as the material of the intermediate metal plate layer helps to increase the spot area of ​​the entire battery system; the bipolar plate structural layer (titanium or titanium alloy) and the intermediate metal plate layer (aluminum or aluminum alloy) are combined by welding to form a double-layer structure, which combines the advantages of the two materials, ensures the lightweight and high strength of the bipolar plate, and improves its corrosion resistance. It has low density and light weight. The intermediate metal plate layer is fully wrapped in the bipolar plate structural layer, which helps to further enhance the overall strength and stability of the bipolar plate, and can also effectively prevent the intermediate metal plate layer from direct contact with the external environment, thereby reducing its risk of corrosion. There is an atomic diffusion layer at the bonding interface between the upper surface and the lower surface of the intermediate metal plate layer and the bipolar plate structural layer. The presence of the atomic diffusion layer can effectively enhance the bonding strength between the intermediate metal plate layer and the bipolar plate structural layer. The surface of the bipolar plate structural layer is formed into a plurality of flow channels by stamping, and the corners at the bottom of the flow channel and the corners at the opening are both set as chamfered structures; the chamfered structures at the bottom of the flow channel and the opening can optimize the flow characteristics of the fluid, reduce the resistance and eddy current of the fluid in the flow channel, improve the fluid transmission efficiency, and help improve the performance of the bipolar plate; at the same time, the chamfer can effectively disperse the stress at the corners and reduce the risk of deformation and rupture of the material during the stamping process.

[0033] The thickness setting of the bipolar plate will affect the conduction path and distribution of the current. The PEM electrolyzer will generate heat during operation. The thickness setting of the bipolar plate will help conduct and dissipate the heat. Thicker bipolar plates can provide better thermal conductivity, help maintain the temperature stability of the electrolyzer, and prevent performance degradation caused by overheating or excessive local temperature. The bipolar plate used in the PEM electrolyzer needs to withstand the pressure and stress inside the electrolyzer. Reasonable thickness setting can enhance the mechanical strength of the bipolar plate and improve its ability to resist deformation, cracking and wear, thereby extending the service life of the electrolyzer. The total thickness of the metal composite bipolar plate described in the preferred embodiment of the present application is 2~12mm, and the preferred thickness is 4-10mm. In order to adjust the balanced corrosion resistance, thermal conductivity and cost of the bipolar plate, further, the ratio of the thickness of each layer of the bipolar plate structure layer to the thickness of the intermediate metal plate layer is 1: (2~4), and preferably, the ratio of the two is 1:4.

[0034] In the embodiment of the present application, the upper and lower surfaces of the intermediate metal plate layer are respectively welded with bipolar plate structural layers, and an atomic diffusion layer is formed between the two plates during the welding process. The atomic diffusion layer serves as a bridge connecting the intermediate metal plate layer and the bipolar plate structural layer, and its thickness directly affects the bonding strength between the two metal plates. A thicker atomic diffusion layer can provide a larger contact area and a stronger interaction force, thereby enhancing the bonding strength; an overly thick atomic diffusion layer can also lead to stress concentration and increased residual stress during welding, which in turn reduces the bonding strength. At the same time, since the bipolar plate may be subjected to various external forces and internal stresses during use, the thickness of the atomic diffusion layer will affect the overall stiffness and strength of the bipolar plate, thereby affecting its anti-deformation ability; a thicker atomic diffusion layer can provide better support and restraint, thereby improving the anti-deformation ability of the bipolar plate. In addition, the thickness of the atomic diffusion layer will also affect the electrochemical performance of the bipolar plate, as shown in the following: a thinner atomic diffusion layer can reduce the transmission resistance of electrons between the two metal plates, thereby improving the conductivity, but if the atomic diffusion layer is too thin and has unfavorable factors such as defects or pores, it will lead to the interruption of the electron transmission path or the increase of resistance. During the electrochemical reaction, the thickness of the atomic diffusion layer will also affect the polarization phenomenon of the bipolar plate; a thicker atomic diffusion layer may increase the transmission distance and time of ions and electrons between the two layers of metal plates, thereby increasing the polarization resistance and intensifying the polarization phenomenon. Therefore, when selecting the thickness of the atomic diffusion layer, it is necessary to comprehensively consider factors such as its bonding strength, deformation resistance, fatigue life, conductivity, corrosion resistance and polarization phenomenon. In the embodiment of the present application, the average thickness of the atomic diffusion layer is 5~20μm, which can provide good mechanical properties and electrochemical performance.

[0035] In the embodiments of the present application, the size of the flow channel set on the bipolar plate structure has an important influence on the performance of the bipolar plate, and the flow channel width directly affects the flow speed and distribution of the gas in the flow channel. A wider flow channel can not only reduce the gas flow resistance, promote uniform distribution of gas, and enable the gas to pass through the flow channel more smoothly, but also facilitate stamping and improve the yield rate; however, an overly wide flow channel may cause material waste and increase processing difficulty, and is also not conducive to the effective transfer of gas to the membrane electrode. The depth of the flow channel will also affect the diffusion efficiency of the gas to the diffusion layer and the mass transfer process inside the electrolyzer. A deeper flow channel can increase the contact area between the gas and the diffusion layer, which is conducive to better diffusion of the gas into the catalyst layer to participate in the reaction; however, an overly deep flow channel will hinder the effective transfer of gas to the membrane electrode. Therefore, ensure the effective flow and distribution of the gas in the flow channel, avoid material waste and increased processing difficulty caused by an overly wide flow channel; at the same time, in order to balance the gas diffusion and mass transfer efficiency, ensure the stable performance of the electrolyzer. In some embodiments of the present application, the width of the flow channel is 1.2~2.0mm and the depth is 0.5~0.8mm. The angle between the side and bottom of the flow channel will affect the flow path and resistance of the gas in the flow channel. A larger angle can make the gas flow smoother and reduce the flow resistance, thereby improving the performance of the electrolyzer. At the same time, the size of this angle also affects the structural strength of the bipolar plate. A smaller angle will increase the stress concentration at the bottom of the flow channel and reduce the deformation resistance of the bipolar plate. A larger angle will help disperse the stress and improve the structural strength of the bipolar plate. Therefore, in some embodiments of the present application, in order to optimize the flow performance and structural strength of the bipolar plate and improve the overall performance and stability of the electrolyzer, the angle formed by the side and bottom of the flow channel is controlled to be 135°~175°.

[0036] As a further preferred solution, the flow channel described in the embodiment of the present application is divided into a gas transition zone, a reaction zone and a drainage transition zone on the surface of the bipolar plate structure layer; wherein the gas transition zone adopts a multi-branch mesh flow field, the reaction zone adopts a wavy flow field, and the drainage transition zone adopts a point flow field structure. In this solution, the multi-branch mesh flow field design of the gas transition zone helps to evenly distribute the input gas (such as hydrogen, oxygen, etc.) or liquid (such as water, etc.) to the entire reaction zone, maintain the stable flow of gas in the flow channel, avoid the accumulation of gas or liquid in a certain area or the formation of a dead zone, and can provide more gas diffusion paths, promote the diffusion of gas molecules to the electrolyte and the catalyst layer, help to accelerate the reaction rate, and improve the overall performance of the electrolyzer. The wavy structure of the reaction zone helps to evenly distribute and transfer heat and prevent local overheating or overcooling. The point flow field structure of the drainage transition zone can guide the water or electrolyte generated by the reaction to flow from the reaction zone to the outlet of the water outlet, prevent the occurrence of flooding, keep the reaction zone dry and operate efficiently, avoid the accumulation of fluid in the drainage transition zone, and help maintain the long-term stability and efficiency of the electrolyzer.

[0037] As a further preferred solution, the metal composite bipolar plate described in the embodiment of the present application is provided with a water inlet hole on one side and a water outlet hole on the other side, the water inlet hole and the water outlet hole are located at diagonal positions of the metal composite bipolar plate, the water inlet and the water outlet are at diagonal positions to each other, and the flow channel connects the water inlet hole and the water outlet hole; it is convenient for heat to be transferred to the entire bipolar plate. The metal composite bipolar plate is also provided with air holes for gas to pass through.

[0038] The present application also provides a method for processing a metal composite bipolar plate, which solves the problem that the flow channel corners are prone to cracking or warping during the stamping process by improving the stamping method, and combines welding and annealing to improve the performance of the bipolar plate. The processing method includes the following steps: Pretreatment: Cut the intermediate metal sheet and bipolar plate sheet to the appropriate size, clean and ensure that the surface of the intermediate metal sheet and bipolar plate sheet is clean and pollution-free; Stamping: Stamp the bipolar plate sheet in steps to form a flow channel on its surface, so that the corners at the bottom of the flow channel and the intersections at the opening are chamfered to obtain a bipolar plate structure layer; Welding composite: fix the middle metal plate, place the bipolar plate structure layer plates on the upper and lower surfaces of the middle metal plate respectively, weld the bipolar plate structure layer plates and the middle metal plate together by welding, and wrap the middle metal plate inside the bipolar plate structure layer to obtain a composite metal plate with a bipolar plate structure; Annealing treatment: the composite metal plate is subjected to annealing treatment, and after cooling, a metal composite bipolar plate is obtained.

[0039] As a further preferred solution, in the pretreatment process of the processing method, ultrasonic cleaning is used to clean the intermediate metal plate and the bipolar plate, and the cleaning medium is analytical pure anhydrous ethanol.

[0040] Due to stress concentration and uneven material flow, cracking and warping problems are prone to occur at the corners of the flow channel. These problems not only affect the appearance quality of the bipolar plate, but more importantly, they also reduce its structural strength and fluid transmission performance. In the embodiments of the present application, through the step-by-step stamping design, the flow and deformation of the material can be more accurately controlled to avoid these problems; in particular, the chamfer design can effectively disperse the stress at the corners, reduce the deformation and cracking risks of the material during the stamping process, and at the same time increase the strength at the corners of the flow channel and improve the overall structural stability of the bipolar plate. During the stamping process, the plate will continue to be unevenly thinned, and dangerous sections are prone to appear at locations with large thinning, increasing the risk of cracking; therefore, the blank holder force is an important parameter that needs to be accurately controlled during the stamping process of the bipolar plate. The magnitude of the pressure directly affects the degree of plastic deformation and the molding quality of the plate. If the blank holder force is too small, the plate cannot be fully deformed, resulting in inaccurate or incomplete flow channel shape; on the contrary, if the blank holder force is too large, the local stress of the plate may exceed its tensile strength, resulting in cracking. The stamping speed is also an important factor affecting the quality of bipolar plate stamping. The speed of the stamping speed will directly affect the deformation rate and stress distribution of the plate. If the stamping speed is too fast, the deformation rate of the plate will increase, which may lead to stress concentration and increased risk of rupture; at the same time, too fast a stamping speed will also cause the plate to rebound greatly during the forming process, affecting the dimensional accuracy and performance of the product; on the contrary, if the stamping speed is too slow, although the risk of rupture can be reduced, the production cycle and cost will be increased. Therefore, it is necessary to reasonably select the stamping speed while ensuring the quality of the forming. Preferably, the partial stamping forming process includes: the first step of stamping uses a first punch with a semicircular or arc-shaped end to stamp simultaneously on the upper and lower surfaces of the bipolar plate plate. In this step, it is ensured that the plate can start plastic deformation but does not produce excessive stress. Therefore, it is necessary to ensure that the blanking force is moderate. In the embodiment of the present application, the blanking force of the first step of stamping is set to 300kN~350kN; in order to avoid stress concentration and rupture caused by too fast, or too slow to affect production efficiency, in this step, the stroke is 40~65SPM. In the second step, the second punch with the first arc chamfered end is used to punch simultaneously on the upper and lower surfaces of the plate. As the punching progresses, the deformation of the plate increases. Therefore, the blank holding force in the second step needs to be appropriately increased. The increase in pressure should be controlled within a certain range to avoid plate rupture. In this step, the blank holding force is set to 320kN~360kN; the stroke is 40~65SPM.The third punch with a second arc chamfered end is used in the third step of stamping to stamp simultaneously on the upper and lower surfaces of the plate. Since the plate has undergone deformation in the first two steps, a greater pressure is required to complete the final forming, but it is necessary to reasonably control the blanking force under the premise of ensuring the forming quality; the stamping speed also needs to be further increased, and the increase in the stamping speed should avoid excessive rebound and dimensional error; in this step, the blanking force is set to 320kN~380kN, and the stroke is 40~65SPM. The size and shape of the chamfer will directly affect the forming accuracy of the flow channel. After stamping, the plate may rebound. Therefore, in order to obtain an accurate flow channel shape, effectively control the rebound amount, and improve the dimensional accuracy of the product, it is necessary to reasonably design the chamfer radius and the punch width. Preferably, in the second step of stamping, the radius r1 of the first arc chamfer and the width L2 of the second punch meet r1=1 / 4L2, and the radius r1 of the first arc chamfer is relatively large, which helps to reduce the resistance and the risk of plate rupture during the stamping process, while ensuring the basic shape and dimensional accuracy of the flow channel. In the third step of stamping, a smaller arc chamfer radius is used to make the corners of the flow channel smoother, reduce the resistance inside the flow channel, and improve the flow efficiency of the fluid; in the third step of stamping, the radius r2 of the second arc chamfer and the width L3 of the third punch satisfy r2=1 / 9L3; in the third step of stamping, it helps to further control the deformation of the sheet and ensure the precise forming of the flow channel. Therefore, in the process of partial stamping, by adjusting the stamping steps and parameters, the shape, size and distribution of the flow channel can be flexibly controlled to meet the needs of different application scenarios. During stamping, the corners at the bottom of the flow channel and the corners at the opening are chamfered, which can not only optimize the flow characteristics of the fluid and reduce fluid resistance, but also solve the problem of easy cracking and warping at the corners of the flow channel in the traditional stamping process; improve the yield rate of bipolar plate products.

[0041] As a further preferred solution, the intermediate metal sheet described in the processing method is an aluminum or aluminum alloy plate, and the bipolar plate structural layer plate is a titanium or titanium alloy plate; laser welding is used in the welding composite. During welding, if the laser power is too low, the weld will not be fully melted, while if it is too high, the material will be excessively ablated or defective. The laser power is 4~6kW, and the spot diameter is 0.18~0.25mm. Titanium-aluminum alloy is prone to thermal stress during processing, resulting in an increased risk of deformation and cracking. Preheating treatment can reduce the thermal stress of the material during processing, thereby reducing the risk of deformation and cracking, and ensuring the forming quality and precision of the titanium-aluminum composite bipolar plate. By reasonably controlling the preheating temperature, the processing performance of the material can be significantly improved, the uniform distribution of alloy elements can be promoted, the quality and strength of the welded joint can be improved, the microstructure of the material can be optimized, and the corrosion resistance of the material can be improved. Therefore, in the embodiment of the present application, the intermediate metal sheet and the bipolar plate structural layer plate are preheated before welding, and the preheating temperature is controlled between 350℃ and 450℃.

[0042] As a further preferred solution, the intermediate metal plate described in the processing method is an aluminum or aluminum alloy plate, and the bipolar plate plate is a titanium or titanium alloy plate; when the welding composite is used, when diffusion welding is adopted, a suitable welding temperature can ensure the thickness of the diffusion layer, but too high a temperature may cause excessive growth of grains, forming a coarse grain structure, which will have an adverse effect on the mechanical properties of the joint. In the embodiment of the present application, the welding temperature is set to 540~560℃. At this temperature, titanium and aluminum atoms can diffuse sufficiently to form an atomic diffusion layer of a certain thickness. The diffusion layer is the basis of titanium-aluminum metallurgical bonding and helps to enhance the bonding strength of the bipolar plate; and at this temperature, intermetallic compounds, such as TiAl3, can be controlled within a suitable range to enhance the hardness and wear resistance of the joint, and avoid excessive intermetallic compounds causing embrittlement of the joint and reducing its plasticity and toughness. Welding pressure is an important factor in determining the strength of the titanium-aluminum interface. A pressure of 5.5-7 MPa helps to achieve close contact between the titanium-aluminum interface, reduce voids and defects at the interface, and thus improve the bonding strength of the joint. At the same time, it can promote diffusion and metallurgical bonding between atoms, further enhance the performance of the joint, and avoid the formation of interface diffusion voids during welding. These voids may reduce the mechanical properties and electrical conductivity of the joint. The welding time also affects the firmness of the titanium-aluminum bond. Too short a time may lead to insufficient atomic diffusion, affecting the bonding strength of the joint; while too long a time may lead to grain growth and thickening of intermetallic compounds, reducing the mechanical properties of the joint. In the embodiment of the present application, the welding time is 60-90 minutes. During this time, the titanium and aluminum atoms can be fully diffused and bonded at the interface, thereby forming a firm metallurgical connection.

[0043] In the processing method of metal composite bipolar plates, annealing is a key step, which has a significant impact on the performance of titanium aluminum composite bipolar plates. The impact on shear strength is as follows: when the annealing temperature is high and the holding time is moderate, the shear strength of the titanium aluminum composite plate will gradually rise to a peak value; however, if the holding time is too long, the interface shear strength will begin to decrease. In terms of tensile strength and plasticity, at a higher annealing temperature, if the holding time is too long, it will lead to a decrease in ultimate tensile strength and a decrease in plasticity. In terms of the impact on microstructure, at a higher annealing temperature, the grains in the titanium aluminum composite plate will grow, and the growth of the grains may affect the mechanical properties and processing properties of the material. At a higher annealing temperature and appropriate holding time, the intermediate compound TiAl3 may be generated in the interface bonding area, and the content of this compound has an important influence on the microstructure and performance of the bipolar plate bonding interface. In addition, annealing can also improve the mechanical properties and processing properties of titanium aluminum alloys, making them have better strength and toughness; but improper annealing conditions will lead to a decrease in the processing properties of the material. Therefore, in the embodiment of the present application, during the annealing treatment described in the processing method, the annealing protective gas is 99.99% argon, the annealing temperature is set to 480°C to 520°C, and the duration is 20min to 30min. Under the conditions of this annealing temperature and annealing time, a bipolar plate with excellent mechanical properties can be obtained.

[0044] The embodiments of the present application also provide an application of a metal composite bipolar plate in manufacturing a PEM electrolyzer.

[0045] The following are some embodiments of the present application, and the present application is further described through the following embodiments.

[0046] Example 1

[0047] like Figure 1 The present embodiment provides a metal composite bipolar plate, comprising an intermediate metal plate layer 10, wherein the upper surface and the lower surface of the intermediate metal plate layer are respectively welded with a bipolar plate structure layer 20, wherein the intermediate metal plate layer 10 is made of 6061 aluminum alloy, and the bipolar plate structure layer 20 is made of TA1 titanium alloy; the intermediate metal plate layer 10 is fully wrapped in the bipolar plate structure layer 20, and an atomic diffusion layer exists at the bonding interface between the upper surface and the lower surface of the intermediate metal plate layer 20 and the bipolar plate structure layer 20, and the average thickness of the atomic diffusion layer is 5.13 μm; a plurality of flow channels 21 are formed on the surface of the bipolar plate structure layer 20 by stamping, and the corners at the bottom of the flow channel 21 and the corners at the opening are both set as chamfered structures; the width of the flow channel is 2.0 mm, and the depth is 0.8 mm; the angle formed by the side of the flow channel and the bottom is 150°.

[0048] The processing method of the metal composite bipolar plate is as follows: Pretreatment: The intermediate metal sheet and the bipolar plate are cut to appropriate sizes, and the intermediate metal sheet and the bipolar plate are cleaned by ultrasonic wave. The cleaning medium is analytical pure anhydrous ethanol, so that the surface of the metal material used is clean and pollution-free; Stamping: The bipolar plate is stamped in steps to form a flow channel on its surface, so that the corners at the bottom of the flow channel and the intersection of the opening are chamfered to obtain a bipolar plate structure layer; the step-by-step stamping is divided into three steps. In the first step, a first punch with a semicircular or arc-shaped end is used to stamp the upper and lower surfaces of the bipolar plate at the same time. The blanking force of the stamping is set to 300kN and the stroke is 50SPM; in the second step, a second punch with a first arc-shaped chamfered end is used to stamp the upper and lower surfaces of the bipolar plate at the same time. The lower surface is punched simultaneously, the blanking force is set to 320kN, the stroke is 50SPM, and the relationship between the radius r1 of the first arc chamfer and the width L2 of the second punch is r1=1 / 4L2; the third step of punching uses a third punch with a second arc chamfer at the end to punch simultaneously on the upper and lower surfaces of the plate, the blanking force is set to 330kN, the stroke is 50SPM, and the relationship between the radius r2 of the second arc chamfer and the width L3 of the third punch satisfies r2=1 / 9L3; Welding composite: fix the middle metal sheet, place the bipolar plate structure layer plates on the upper and lower surfaces of the middle metal sheet respectively, and weld the bipolar plate structure layer plates and the middle metal sheet with laser welding. The laser power is 5.5kW and the spot diameter is 0.20mm. The middle metal sheet is wrapped inside the bipolar plate structure layer to obtain a composite metal plate with a bipolar plate structure. Annealing treatment: the composite metal plate is subjected to annealing treatment, the annealing protective gas is 99.99% argon, the annealing temperature is set to 490° C., the duration is 30 min, and the metal composite bipolar plate is obtained after cooling.

[0049] The performance of the metal composite bipolar plate described in the above-mentioned Example 1 was tested, and the specific test items and the adopted test methods / standards are shown in Table 1 below. Figure 3 This is a cross-sectional SEM image of the metal composite bipolar plate described in this embodiment.

[0050] Table 1: Performance test results of the metal composite bipolar plate of Example 1 Serial number Test items Test method / standard Test results 1 Interface bonding strength (MPa) GBT32468-2015 26.96 2 Tensile strength (MPa) GBT32468-2015 144.56 3 Yield strength (MPa) GBT32468-2015 98.28 4 Density (g / cm³) GBT20042.6-2024 3.2 5 Resistance (µΩ·cm) GBT20042.6-2024 17.2 6 Corrosion current density (μA / cm²) GBT20042.6-2024 0.74 7 Elongation (%) GBT32468-2015 12.6% On the basis of the above-mentioned Example 1, the influence of the blank holder force of each step on the runner rebound force and the rupture at the corner during the step-by-step stamping was further discussed. Different blank holder forces were set, but other conditions were kept consistent with Example 1, and a scheme of using one-time stamping was set as a comparative example (other conditions were the same as those in the example, only one-time stamping was used in the stamping step, and the blank holder force and stamping speed were the same as those of the second step of stamping in Example 1). The specific stamping speed settings and comparison results are shown in Table 2.

[0051] Table 2: Effect of stroke on runner stamping results Serial number First step blank holding force (kN) Second step blank holding force (kN) The third step: Blank holding force (kN) Channel corner rupture ratio (%) 1 250 300 310 0 2 250 320 320 0 3 250 340 350 0 4 250 360 380 0 5 250 380 400 0.6 6 300 300 310 0 7 300 320 320 0 8 300 340 350 0 9 300 360 380 0 10 300 380 400 0.7 11 320 300 310 0 12 320 320 320 0 13 320 340 350 0 14 320 360 380 0 15 320 380 400 1.7 16 350 300 310 0 17 350 320 320 0 18 350 340 350 0 19 350 360 380 0 20 350 380 400 2.1 21 380 300 310 0.4 22 360 320 320 0.9 23 360 340 350 1.6 24 360 360 380 2.9 25 360 380 400 5.1 The results in Table 2 show that as the blanking force increases, the fracture ratio begins to rise, especially when the blanking force reaches 400 kN in the third step, the fracture ratio increases significantly. However, when the blanking force is provided in a smaller range, it is difficult for the bipolar plate structure to achieve the expected shape during stamping.

[0052] On the basis of the above-mentioned Example 1, the influence of the stroke of each step on the flow channel rebound force and the rupture at the corner during step-by-step stamping was further discussed, and different stroke ranges were set, but other conditions remained the same as in Example 1. See Table 3 for specific stroke settings and comparison results.

[0053] Table 3: Effect of stroke on runner stamping effect Serial number Stroke (SPM) Corner fracture ratio (%) 1 40 0 2 45 0 3 50 0 4 55 0 5 60 0 6 65 0 7 70 0.3 8 75 0.4 9 80 0.5 In this experiment, it was found that when the stroke was controlled at less than 40 SPM, the stamping effect could not meet the expected requirements. When the stroke was controlled to exceed 65 SPM, a certain number of the experimental samples broke or cracked to varying degrees at the corners.

[0054] On the basis of the above-mentioned Example 1, the influence of annealing temperature on the performance of the bipolar plate was further discussed, and different annealing temperatures were set, but other conditions remained the same as in Example 1. See Table 4 for specific welding speed settings and comparison results.

[0055] Table 4: Effect of annealing temperature on bipolar plate performance Serial number Annealing temperature (℃) Interface bonding strength (MPa) Tensile strength (MPa) Yield strength (MPa) 1 420 19.12 141.64 96.37 2 450 19.97 144.27 97.22 3 480 20.4 140.68 98.20 4 490 26.96 144.56 98.28 5 500 28.84 145.07 99.64 6 520 26.97 144.23 98.73 7 550 21.16 144.30 97.76 The results in Table 4 above show that: from 420℃ to 490℃, the interface bonding strength gradually increases and reaches 26.9 MPa; then, as the annealing temperature increases to 500℃, the interface bonding strength shows an upward trend; at 520℃ and 550℃, the interface bonding strength decreases significantly, indicating that when the annealing temperature is too high, the microstructure of the interface and the types and proportions of intermetallic compounds are affected. The interface bonding strength reaches the optimum when annealing at 500℃, indicating that the interface bonding of the material is the strongest at this temperature. It shows a high tensile strength at 490℃-520℃. When the temperature exceeds 520℃, both the tensile strength and the yield strength show a downward trend. This may be because the excessively high annealing temperature will cause the grains inside the material to grow, reduce the dislocation density, and thus weaken the deformation strengthening effect. From 420℃ to 490℃, the yield strength fluctuates slightly, but the change is small; at 500℃, the yield strength reaches the maximum value.

[0056] On the basis of the above-mentioned Example 1, the influence of laser welding conditions on the performance of the bipolar plate was further discussed, and different laser welding conditions were set, but other conditions remained the same as in Example 1. See Table 5 for specific welding condition settings and performance results.

[0057] Table 5: Effect of laser welding conditions on bipolar plate performance Serial number Laser power (kW) Spot diameter (mm) Interface bonding strength (MPa) Tensile strength (MPa) Yield strength (MPa) 1 3 0.15 19.01 141.76 96.41 2 3 0.18 19.50 142.05 97.33 3 3 0.20 19.88 142.22 98.20 4 3 0.25 20.59 142.48 98.63 5 3 0.30 19.56 141.31 98.85 6 4 0.15 21.12 142.10 97.00 7 4 0.18 24.45 142.54 98.66 8 4 0.20 27.42 144.54 99.30 9 4 0.25 24.93 144.75 98.75 10 4 0.30 20.69 142.95 97.62 11 5 0.15 20.62 142.62 97.93 12 5 0.18 26.14 144.90 98.18 13 5 0.20 29.23 145.08 99.60 14 5 0.25 26.94 143.76 98.96 15 5 0.30 21.04 141.65 98.12 16 6 0.15 19.02 140.72 96.73 17 6 0.18 26.41 143.21 98.65 18 6 0.20 28.28 144.22 99.54 19 6 0.25 25.74 144.11 98.01 20 6 0.30 21.39 141.86 97.98 21 7 0.15 17.51 14055 95.83 22 7 0.18 20.20 140.41 96.80 23 7 0.20 24.20 141.19 98.02 24 7 0.25 26.32 142.79 98.19 25 7 0.30 22.59 140.02 97.61 The metal composite bipolar plate described in the embodiment of the present application is applied to the proton exchange membrane (PEM) electrolyzer system. According to the experimental test results, when the interface bonding strength of the metal composite bipolar plate is above 22 MPa, the performance of the bipolar plate meets the application requirements. It can be seen from the performance test results in Table 5 above that when the laser power remains unchanged, the relationship between the interface bonding strength of the bipolar plate and the spot diameter is that within a certain range, the interface bonding strength increases with the increase of the spot diameter, but when the spot diameter reaches a critical value, the interface bonding strength will decrease accordingly. This may be due to the fact that the spot is too large, the energy density is significantly reduced, which may cause the titanium aluminum sheet to not be fully penetrated, and the insufficient diffusion of elements makes the atomic diffusion layer too thin, resulting in a decrease in the interface bonding strength. The effect of laser power on the interface bonding strength of the bipolar plate is manifested as follows: under the same spot setting, the interface bonding strength increases roughly with the increase of laser power, but there are also abnormal situations. For example, when the laser power reaches 7kW, the spot is between 0.15 and 0.18, showing a smaller interface bonding strength. This may be due to the uneven distribution of welding energy under the conditions of high power and small spot, and the microstructure of the metal organization at the bonding interface is affected, such as insufficient diffusion of metal atoms and grain coarsening, which affect the interface bonding strength. The results in Table 5 show that when the laser power is in the range of 4-6kW and the spot diameter is in the range of 0.18-0.25mm, the interface bonding strength of the bipolar plate is ≥22MPa, which meets the application requirements. Experiments show that the tensile strength and yield strength of the metal composite bipolar plate obtained in the embodiment of the present application are better in the range of laser power of 4~6kW and spot diameter of 0.18~0.25mm.

[0058] Example 2

[0059] The present embodiment provides a metal composite bipolar plate, comprising an intermediate metal plate layer, wherein the upper surface and the lower surface of the intermediate metal plate layer are respectively welded with a bipolar plate structural layer, wherein the intermediate metal plate layer material is 6063 aluminum alloy, and the bipolar plate structural layer material is TA1 titanium; the intermediate metal plate layer is fully wrapped in the bipolar plate structural layer, and an atomic diffusion layer exists at the bonding interface between the upper surface and the lower surface of the intermediate metal plate layer and the bipolar plate structural layer, and the average thickness of the atomic diffusion layer is 8.62 μm; a plurality of flow channels are formed on the surface of the bipolar plate structural layer by stamping, and the corners at the bottom of the flow channel and the corners at the opening are both set as chamfered structures; the width of the flow channel is 1.6 mm, and the depth is 0.8 mm; and the angle formed by the side of the flow channel and the bottom is 165°.

[0060] The processing method of the metal composite bipolar plate is as follows: Pretreatment: The intermediate metal sheet and the bipolar plate are cut to appropriate sizes, and the intermediate metal sheet and the bipolar plate are cleaned by ultrasonic wave. The cleaning medium is analytical pure anhydrous ethanol, so that the surface of the metal material used is clean and pollution-free; Stamping: The bipolar plate is stamped in steps to form a flow channel on its surface, so that the corners at the bottom of the flow channel and the intersection of the opening are chamfered to obtain a bipolar plate structure layer; the step-by-step stamping is divided into three steps. In the first step, a first punch with a semicircular or arc-shaped end is used to stamp the upper and lower surfaces of the bipolar plate at the same time. The blanking force of the stamping is set to 330kN and the stroke is 45SPM; in the second step, a second punch with a first arc-shaped chamfered end is used to stamp the upper and lower surfaces of the bipolar plate at the same time. The lower surface is punched simultaneously, the blanking force is set to 350kN, the stroke is 45SPM, and the relationship between the radius r1 of the first arc chamfer and the width L2 of the second punch is r1=1 / 4L2; the third step of punching uses a third punch with a second arc chamfer at the end to punch simultaneously on the upper and lower surfaces of the plate, the blanking force is set to 380kN, the stroke is 45SPM, and the relationship between the radius r2 of the second arc chamfer and the width L3 of the third punch satisfies r2=1 / 9L3; Welding composite: fix the middle metal plate, place the bipolar plate structure layer plates on the upper and lower surfaces of the middle metal plate respectively, and weld the bipolar plate structure layer plates and the middle metal plate with diffusion welding. The welding temperature is set to 550°C, the pressure is 6.0MPa, and the welding time is 80min, so that the middle metal plate is wrapped inside the bipolar plate structure layer to obtain a composite metal plate with a bipolar plate structure; Annealing treatment: the composite metal plate is subjected to annealing treatment, the annealing protective gas is 99.99% argon, the annealing temperature is set to 500° C., the duration is 30 min, and the metal composite bipolar plate is obtained after cooling.

[0061] The performance of the metal composite bipolar plate described in the above Example 2 was tested, and the specific test items and the adopted test methods / standards are shown in Table 6 below.

[0062] Table 6: Performance test results of the metal composite bipolar plate of Example 2 Serial number Test items Test methods / standards used Test results 1 Interface bonding strength (MPa) GBT32468-2015 26.4 2 Tensile strength (MPa) GBT32468-2015 147.3 3 Yield strength (MPa) GBT32468-2015 99.3 4 Density (g / cm³) GBT20042.6-2024 3.18 5 Resistance (µΩ·cm) GBT20042.6-2024 24.8 6 Corrosion current density (μA / cm²) GBT20042.6-2024 0.23 7 Elongation (%) GBT32468-2015 12.1% On the basis of the above-mentioned Example 2, the influence of diffusion welding conditions on the performance of the bipolar plate was further discussed, and different diffusion welding conditions were set, but other conditions remained the same as in Example 2. See Table 7 for specific welding condition settings and results.

[0063] Table 7: Effect of diffusion welding conditions on bipolar plate performance Serial number Soldering temperature (℃) Pressure (MPa) Welding time (min) Interface bonding strength (MPa) Tensile strength (MPa) Yield strength (MPa) 1 530 5.0 50 16.91 140.90 95.46 2 530 5.5 60 18.54 140.69 96.15 3 530 6.5 80 19.37 140.10 97.77 4 530 7.0 90 21.92 141.11 97.86 5 530 7.5 100 19.51 141.90 97.29 6 540 5.0 50 20.24 140.47 97.80 7 540 5.5 60 22.73 144.15 98.12 8 540 6.5 80 26.64 144.97 98.72 9 540 7.0 90 25.52 144.60 98.31 10 540 7.5 100 21.26 141.43 98.06 11 550 5.0 50 21.43 142.16 97.78 12 550 5.5 60 25.90 143.33 98.58 13 550 6.5 80 28.03 145.75 99.39 14 550 7.0 90 28.2 145.20 99.65 15 550 7.5 100 24.3 140.41 98.78 16 560 5.0 50 21.82 141.10 97.45 17 560 5.5 60 27.10 144.09 98.35 18 560 6.5 80 28.12 144.88 99.47 19 560 7.0 90 28.33 145.11 99.92 20 560 7.5 100 24.46 141.73 98.29 21 570 5.0 50 20.93 140.13 97.53 22 570 5.5 60 21.21 141.51 98.72 23 570 6.5 80 26.47 143.62 98.77 24 570 7.0 90 25.80 142.78 98.96 25 570 7.5 100 21.91 141.44 97.54 The results in Table 7 above show that when the welding temperature is set to 540~560℃, the interface bonding strength of the bipolar plate is greater than 22MPa, which meets the application requirements. This is because when the welding temperature is 540~560℃, the diffusion coefficient of titanium and aluminum atoms is significantly improved, which promotes the mutual diffusion of interface elements, thereby prompting the formation of a metal atomic diffusion layer and reaching a suitable thickness. Since the interface oxide (Al2O3 / TiO2) fragmentation rate increases under a pressure of 5.5~6.5MPa, the interface bonding strength can basically be maintained above 22MPa when the welding pressure is 5.5-7.0MPa under constant temperature. However, with the increase of welding pressure, the metal flow at the interface intensifies, which may introduce microcracks. Therefore, after the welding pressure exceeds 7.0MPa, the interface bonding force is affected and shows a downward trend. The results in Table 7 also show that when the welding temperature is 540~560℃, the welding pressure is 5.5~6.5MPa, and the welding time is 60-90min, the tensile strength and yield strength are also good.

[0064] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A metal composite bipolar plate, characterized in that: It includes an intermediate metal plate layer, the upper surface and the lower surface of the intermediate metal plate layer are respectively welded with a bipolar plate structure layer, the intermediate metal plate layer is fully wrapped in the bipolar plate structure layer, the intermediate metal plate layer material is aluminum or aluminum alloy, and the bipolar plate structure layer material is titanium or titanium alloy; an atomic diffusion layer exists at the bonding interface between the upper surface and the lower surface of the intermediate metal plate layer and the bipolar plate structure layer; a plurality of flow channels are formed on the surface of the bipolar plate structure layer by stamping, and the corners at the bottom of the flow channel and the corners at the opening are both set as chamfered structures.

2. The metal composite bipolar plate according to claim 1, characterized in that: The total thickness is 2-12 mm, wherein the ratio of the thickness of each bipolar plate structure layer to the thickness of the middle metal plate layer is 1:(2-4).

3. The metal composite bipolar plate according to claim 1, characterized in that: The average thickness of the atomic diffusion layer is 5-20 μm.

4. The metal composite bipolar plate according to any one of claims 1 to 3, characterized in that: The width of the flow channel is 1.2-2.0 mm, and the depth is 0.5-0.8 mm; the angle formed by the side of the flow channel and the bottom is 135°-175°.

5. The metal composite bipolar plate according to any one of claims 1 to 3, characterized in that: The flow channel is divided into a gas transition zone, a reaction zone and a drainage transition zone on the surface of the bipolar plate structure layer; wherein the gas transition zone adopts a multi-branch mesh flow field, the reaction zone adopts a wavy flow field, and the drainage transition zone adopts a point flow field structure.

6. The metal composite bipolar plate according to any one of claims 1 to 3, characterized in that: A water inlet hole is provided on one side of the metal composite bipolar plate, and a water outlet hole is provided on the other side. The water inlet hole and the water outlet hole are located at diagonal positions of the metal composite bipolar plate, and the flow channel connects the water inlet hole and the water outlet hole; the metal composite bipolar plate is also provided with air holes for gas to pass through.

7. A method for processing a metal composite bipolar plate according to any one of claims 1 to 6, characterized in that: The following steps are included: Pretreatment: Cut the intermediate metal sheet and bipolar plate sheet to the appropriate size, clean and ensure that the surface of the metal material is clean and free of pollution; Stamping: Stamp the bipolar plate sheet in steps to form a flow channel on its surface, so that the corners at the bottom of the flow channel and the intersections at the opening are chamfered to obtain a bipolar plate structure layer; Welding composite: fix the middle metal plate, place the bipolar plate structure layer plates on the upper and lower surfaces of the middle metal plate respectively, weld the bipolar plate structure layer plates and the middle metal plate together by welding, and wrap the middle metal plate inside the bipolar plate structure layer to obtain a composite metal plate with a bipolar plate structure; Annealing treatment: the composite metal plate is subjected to annealing treatment, and after cooling, a metal composite bipolar plate is obtained.

8. The processing method according to claim 7, characterized in that: During the pretreatment process, ultrasonic cleaning is used to clean the intermediate metal plate and the bipolar plate, and the cleaning medium is analytical pure anhydrous ethanol.

9. The processing method according to claim 7, characterized in that: The stamping process adopts step-by-step stamping; in the first step, a first punch with a semicircular or arc-shaped end is used to stamp the upper and lower surfaces of the bipolar plate simultaneously, and the clamping force is set to 300kN~350kN, and the stroke is 40~65SPM; in the second step, a second punch with a first arc chamfered end is used to stamp the upper and lower surfaces of the bipolar plate simultaneously, and the clamping force is set to 320kN~360kN, and the stroke is 40~65SPM, and the radius r1 of the first arc chamfer and the width L2 of the second punch satisfy r1=1 / 4L2; in the third step, a third punch with a second arc chamfered end is used to stamp the upper and lower surfaces of the bipolar plate simultaneously, and the radius r2 of the second arc chamfer and the width L3 of the third punch satisfy r2=1 / 9L3, and the clamping force is set to 320kN~380kN, and the stroke is 40~65SPM.

10. The processing method according to claim 7, characterized in that: The intermediate metal plate is an aluminum or aluminum alloy plate, and the bipolar plate structural layer plate is a titanium or titanium alloy plate; laser welding is used in the welding composite, and the welding conditions are: the laser power is 4~6kW, and the spot diameter is 0.18~0.25mm; before welding, the intermediate metal plate and the bipolar plate structural layer plate are preheated, and the preheating temperature is controlled between 350℃~450℃.

11. The processing method according to claim 7, characterized in that: The intermediate metal plate is an aluminum or aluminum alloy plate, and the bipolar plate plate is a titanium or titanium alloy plate; when welding the composite, diffusion welding is adopted, and the welding conditions are: the welding temperature is set to 540-560°C, the pressure is 5.5-7MPa, and the time is 60-90min.

12. The processing method according to claim 7, characterized in that: During the annealing treatment, the temperature is set to 490° C. to 520° C., and the duration is 20 min to 30 min.

13. Use of the metal composite bipolar plate according to any one of claims 1 to 6 in manufacturing a PEM electrolyzer.

Citation Information

Patent Citations

  • Forming method for high-precision metal bipolar plate required by fuel cell

    CN110534765A

  • Metal bipolar plate flow field system of proton exchange film fuel cell

    CN111092240A

  • Fuel cell bipolar plate with metal-graphite composite structure and fuel cell

    CN111384413A

  • Coolant flow field design for fuel cell stacks

    CN1650458A